An DETERMINAN PENGAMBILAN KEPUTUSAN KLINIK KEPERAWATAN DI RSUD ARIFIN ACHMAD PROVINSI RIAU : Pengambilan Keputusan Klinik Keperawatan - Rizanda Machmud; Harmawati; Susi Erianti (STIKes Hang Tuah Pekanbaru, 2019)
Nurses always deal with various clinical problems when caring their patients. Nursing clinical decision making is an evaluation process of nursing care to the patient which evaluated by nurses every day. The phenomenon showed that there was a lack of nurses' ability to make a clinical nursing decision in the nursing process of patients at the Intensive Care Installation (IPI) of Arifin Achmad General Hospital of Riau Province. The study aims were to analyzed the factors related to nursing clinical decision making This research was a quantitative study with used cross-sectional design. Population were all nurses in the intensive care installation consisting of ICU, CVCU and PICU. Sample of this study were 60 nurses which taken by used total sampling technique. Data analyze was used multivariate with logistic regression test. The results showed that the factors related to clinical nursing decision making were length of work and training certificates. Meanwhile age, education and work unit factors were not related to clinical nursing decision making. The most dominant factor related to clinical nursing decision making was length of work (OR = 8.312). The results of this study could be an information for nurses to improving their ability in making clinical nursing decision, nurses competency and work experiences in their work units, so that the quality of nursing care services and the quality of hospital services can be improved.